2012
DOI: 10.1111/j.1365-2141.2012.09241.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum B‐cell maturation antigen is elevated in multiple myeloma and correlates with disease status and survival

Abstract: Summary Although TNFRSF17 (also designated as B‐cell maturation antigen (BCMA)) is expressed on tumour cells in B‐cell malignancies, it has not been found in serum. The present study found that BCMA concentrations were higher in the supernatants of cultured bone marrow mononuclear cells from multiple myeloma (MM) patients than in healthy subjects. Serum BCMA levels were measured in samples from MM patients (n = 209), monoclonal gammopathy of undetermined significance (MGUS) individuals (n = 23) and age‐matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
223
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(240 citation statements)
references
References 51 publications
14
223
2
1
Order By: Relevance
“…13,14 BCMA is expressed on MM cell lines and malignant plasma cells with high prevalence and increased expression levels during disease progression from monoclonal gammopathy of undetermined significance (MGUS) to smoldering myeloma to active MM. [15][16][17][18][19][20][21] BCMA is also expressed on plasmacytoid dendritic cells, which promote MM cell growth, survival and drug resistance. [21][22][23] Expression levels on plasmacytoid dendritic cells are also elevated in MM patients versus normal donors.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 BCMA is expressed on MM cell lines and malignant plasma cells with high prevalence and increased expression levels during disease progression from monoclonal gammopathy of undetermined significance (MGUS) to smoldering myeloma to active MM. [15][16][17][18][19][20][21] BCMA is also expressed on plasmacytoid dendritic cells, which promote MM cell growth, survival and drug resistance. [21][22][23] Expression levels on plasmacytoid dendritic cells are also elevated in MM patients versus normal donors.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that levels were higher among patients with progressive disease (PD) than those with responsive disease and decreased with response to therapy (17). BAFF stimulates normal mouse and human B-cell proliferation, and addition of recombinant human BCMA-Fc (rhBCMA-Fc) abrogates this effect in vitro (18)(19)(20).…”
Section: Introductionmentioning
confidence: 92%
“…Four-week-old male CB17 SCID mice were implanted with human multiple myeloma tumors (LAGk-2, LAGk-1A, or LAGl-1) developed from multiple myeloma patients as previously described (17). Tumors were measured and the formula for an ellipsoid volume was applied [4/3 p x (width/2) 2 x (length/2)].…”
Section: Multiple Myeloma Xenograft Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike BAFF, which also binds BAFF-R besides BCMA and TACI, APRIL binds to BCMA and TACI associated with heparan sulfate proteoglycan (HSPG), that is, CD138/syndecan-1 (Figure 1), suggesting a more PC-specific role of APRIL than BAFF [31]. In addition, serum BCMA is Targeting B-cell maturation antigen in multiple myeloma Review higher in MM patients versus healthy donors, suggesting a new biomarker for monitoring disease status and overall survival of MM patients [32]. All these results indicate an important role for the BCMA/APRIL signaling cascade in the pathophysiology of MM.…”
Section: Bcma Is An Ideal Antigen For Targeted Immunotherapy For MMmentioning
confidence: 99%